2018
DOI: 10.1017/atsip.2018.10
|View full text |Cite
|
Sign up to set email alerts
|

A technical framework for automatic perceptual evaluation of singing quality

Abstract: Human experts evaluate singing quality based on many perceptual parameters such as intonation, rhythm, and vibrato, with reference to music theory. We proposed previously the Perceptual Evaluation of Singing Quality (PESnQ) framework that incorporated acoustic features related to these perceptual parameters in combination with the cognitive modeling concept of the telecommunication standard Perceptual Evaluation of Speech Quality to evaluate singing quality. In this study, we present further the study of the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…1) Intonation Accuracy: Intonation accuracy or pitch accuracy evaluation has been the most common method for singing quality assessment, primarily because studies have shown that intonation accuracy is one of the most important perceptual parameters when music experts assess singing quality [42], [43]. In one of the earliest studies, Lal [44] proposed a pitchbased similarity measure to compare a test singing clip to the reference singing clip.…”
Section: A Reference-dependent Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…1) Intonation Accuracy: Intonation accuracy or pitch accuracy evaluation has been the most common method for singing quality assessment, primarily because studies have shown that intonation accuracy is one of the most important perceptual parameters when music experts assess singing quality [42], [43]. In one of the earliest studies, Lal [44] proposed a pitchbased similarity measure to compare a test singing clip to the reference singing clip.…”
Section: A Reference-dependent Techniquesmentioning
confidence: 99%
“…Although MIDI notes used as the reference approximately represent the sequence of sung notes, they are unable to repre-sent human voice since singing voice comprises of pitch transitions, modulations, and different voice timbres. Therefore, studies for singing quality assessment have explored comparison with an ideal reference singing rendition [46], [47], [43], instead of the MIDI notes of the song. The drawback of this approach is that the choice of an ideal singing rendition is subjective.…”
Section: A Reference-dependent Techniquesmentioning
confidence: 99%
See 3 more Smart Citations